Comparison between Dynamic Stabilization and Instrumented Fusion in the Treatment of Spinal Stenosis with Degenerative Lumbar Scoliosis. (18th May 2022) - Luo, Lei; Liu, Liehua; Li, Pei; Zhao, Chen; Liang, Lichuan; Luo, Fei; Zhou, Qiang; Chen, Yanhong; Fang, Lang
Abstract : Objective . Posterior instrumented fusion is the most widely accepted surgical treatment for spinal stenosis with degenerative lumbar scoliosis (DLS). However, long fusion can affect daily activities due to lumbar stiffness. Dynamic stabilization has been introduced to overcome the drawbacks of fusion in recent years. This study aimed to compare the outcomes of dynamic stabilization (Dynesys system) with posterior instrumented fusion for the management of spinal stenosis with DLS. Methods . This study retrospectively reviewed 65 consecutive patients with spinal stenosis and DLS who were undergoing surgical treatment between January 2013 and December 2017. Among them, 34 patients (Dynesys group) had fenestration decompression and Dynesys stabilization, whereas 31 patients (fusion group) underwent posterior instrumented fusion. Clinical outcomes, radiographic data, and postoperative complications were compared between the two groups. Results . The mean number of fixed segments was 3.6 ± 0.9 in the Dynesys group and 4.2 ± 1.0 in the fusion group. Lower average values of operating time and blood loss were observed in the Dynesys group (P < 0.05 ). At an average follow-up of 42 months, there were no significant differences in the visual analog scale for the leg pain (VASleg ), the scoliosis Cobb's angle, and the lumbar lordosis between the two groups (P > 0.05 ). The visual analog scale for back pain (VASback ), oswestry disability index (ODI), and lumbar stiffness disability index (LSDI) scores of the Dynesys group were lower compared with the fusion group (P < 0.05 ). The range of motion (ROM) of implanted segments was significantly higher in the Dynesys group as compared to the fusion group (P < 0.05 ). The overall complications were less in the Dynesys group, but the difference was not statistically significant (P > 0.05 ). Conclusion . Both dynamic stabilization and instrumented fusion can improve the clinical outcomes of patients with spinal stenosis and mild DLS. Compared to instrumented fusion, dynamic stabilization has the advantages of less invasion and motion preservation.